A novel strategy for developing α + β dual-phase titanium alloys with low Young's modulus and high yield strength. (20th June 2021) - Fu, Yu; Xiao, Wenlong; Wang, Junshuai; Ren, Lei; Zhao, Xinqing; Ma, Chaoli
Graphical abstract: Highlights: A novel strategy for developing Ti alloys with low Young's modulus and high strength is proposed. Modeling work indicates that α + β dual-phase is capable for obtaining low Young's modulus and high strength. Excellent combination of low Young's modulus and high yield strength is achieved in newly developed Ti alloy. The microstructure of developed alloy contains UFG α precipitates and metastable β-matrix. Abstract: In this study, a novel strategy for developing α + β dual-phase titanium alloys with low Young's modulus and high yield strength was proposed, and a Ti-15Nb-5Zr-4Sn-1Fe alloy was developed through theoretical composition design and microstructure manipulation. After hot-rolling and subsequent annealing, a high volume fraction of ultrafine grained α phase embedded in metastable β-matrix was formed in the microstructure as intended. Consequently, this alloy exhibits both low Young's modulus (61 GPa) and high yield strength (912 MPa). The experimental results prove that the proposed strategy is appropriate for developing titanium alloys with superior yield strength-to-modulus ratio than those of conventional metallic biomedical materials. Present study might shed light on the research and development of advanced biomedical titanium alloys with low Young's modulus and high yield strength.